Analysis of sprint related performance indicators in professional youth soccer across age groups & positions - Becirovic, M.; Bischofberger, J.; Kornfeind, P.; Stifter, S.; Baca, A. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The aim of this study was to evaluate the playing intensity distribution among 51 highly trained young elite soccer players across different age groups and position profiles during competitive matches. We recorded and analyzed championship matches of the U15, U16 and U18 youth teams from AKA St. Pölten, focusing on kinematic and physiological parameters during halftime assessments and throughout the entire match duration. The final goal of this research is to equip soccer coaches with valuable insights to accurately prescribe training intensities aligned with competitive scenarios, thereby enhancing overall training control.